Allograft-Prosthetic Composite Reconstruction for Massive Proximal Humeral Bone Loss in Reverse Shoulder Arthroplasty. Issue 1 (January 2018) - Sanchez-Sotelo, Joaquin; Wagner, Eric R.; Houdek, Matthew T.
Abstract : Background: Allograft-prosthetic composite (APC) reconstruction of the humerus represents an appealing surgical technique when implantation of a reverse prosthesis is considered in the setting of substantial proximal humeral bone loss1 -4 . Humeral APCs have been successfully performed in the past with a non-reverse shoulder prosthesis4, 5 . Reconstruction of the proximal part of the humerus with an allograft provides adequate support and fixation for the humeral component, allows restoration of length and lateral offset, and provides an opportunity for soft-tissue reattachment when needed. On the basis of the available peer-reviewed data, healing at the allograft-host junction is reliable, and complication rates, including instability, are relatively low3, 6 . Description: Once the glenoid reverse component has been implanted, a proximal humeral allograft is prepared to receive the humeral component of a reverse arthroplasty. The allograft is procured by our institutional bone and tissue bank, purchased from a number of vendors. The graft is selected after review of the description and radiographs provided by the vendor. The priority is to obtain a graft with sufficient length and soft tissues attached. If possible, the graft selected should have a diameter close to the diameter of the humerus of the recipient. The desired allograft length is selected on the basis of preoperative planning and intraoperative measurements, and the distal portion of the allograft is resected accordingly. Depending on the length of the defect, host bone quality, and surgeon preferences, the humeral component may or may not bypass the host-graft junction. The stem bypasses the host-graft junction for shorter APCs, as well as when the bone quality of the native humerus is compromised. Cemented fixation into the graft is universally used. Compression plating is used for graft-to-host fixation, supplemented by implantation of the stem across the junction in selected cases. Care is taken during the freehand cut to obtain optimal contact and compression. Once the ideal humeral bearing thickness has been selected, the polyethylene bearing is implanted and the joint relocated. If the posterior cuff can be repaired to cuff allograft, sutures are placed prior to relocation and are tied after relocation. Other musculotendinous units, such as the deltoid or pectoralis major, are repaired to the allograft if needed. Alternatives: Implantation of a reverse prosthesis with a proximal humeral metal body (a so-called tumor prosthesis) is the main alternative to proximal humeral APC reconstruction. In patients with shorter defects, adequate soft-tissue tension may be obtained by implanting a glenosphere with a large inferior eccentricity and cementing the humeral component in a more proximal position than is usually performed. Alternatively, when implantation of the glenoid component of a reverse prosthesis is not possible, a hemiarthroplasty-APC construct may be performed1, 4, 5, 7 -10, adding a synthetic sleeve such as an aortic Dacron graft to enhance soft-tissue stability if needed. Rationale: When reverse arthroplasty is performed in the setting of substantial humeral bone loss, the humeral component may be poorly supported and at risk for loosening. In addition, the absence of proximal humeral bone stock may lead to shortening and/or loss of lateral offset. Finally, the posterosuperior cuff, subscapularis, deltoid, and pectoralis tendons may remain detached. The potential consequences of humeral bone loss in the setting of reverse arthroplasty include humeral loosening, dislocation, and poor active motion (particularly poor active elevation). Allograft reconstruction of the proximal part of the humerus provides an opportunity for better support of the component, restoration of humeral length and lateral offset, and attachment sites for the musculotendinous structures around the shoulder, if needed.